Pengaruh keseimbangan kerja-hidup (work-life balance) dan beban kerja terhadap kinerja karyawan - Pitriyani, Amelia; Jaya, Umban Adi (University of Merdeka Malang, 2024)
This research aims to determine the effect of work-life balance and workload on employee performance. This research is descriptive quantitative with a saturated sampling technique (total sample). The data collection method in this research uses raw data obtained through a questionnaire survey. The sample in this study consisted of 30 respondents, employees of Pak Karuk convection in Pamijahan, Bogor Regency. Classic assumption tests include the Normality Test. The data analysis technique uses multiple linear regression analysis, Determination Coefficient (R2), Simultaneous Test (F), Partial Test (T). The results of this research show that work life balance is not proven to have an effect on employee performance, while workload has an effect on employee performance.